Mouth opening range for Jordanian population and its relation to gender, age, height, and weight - Mirvet Mohammed Hawwa (Wolters Kluwer Medknow Publications, 2022)
Aim: Maximum mouth opening (MMO) is an important parameter in the assessment of several clinical situations, and its measured value is documented to have gender, age, and anthropometric variation. Background: This study measures the average value of MMO in a sample of the Jordanian population. MMO might be different for different regions of the world and is important for all dental disciplines. We attempt to find correlations between MMO and body characteristics such as gender, age, body weight, and height. Materials and Methods: A total of 565 Jordanian patients (191 males and 374 females; aged 3-70 years) were randomly selected for this cross-sectional study. Mouth opening was measured using a calibrated ruler between the incisal edges of the upper and lower central incisors (interincisal length), and weight and height were measured using a medical scale. In addition, age and gender were recorded. Patients were informed of the study and agreed to participate. Statistical differences of MMO between male and female patients in each age group were assessed using the t-test, the correlation between the MMO and body weight and height was assessed using a Pearson correlation coefficient and simple linear regression using the SPSS program. Results and Conclusions: The mean MMO across the sample was 45 ± 4.78 mm with a range of 36-61 mm. The mean MMO in males was 45.7 ± 5.2 mm, varied from females, which was 44.65 ± 4.4 mm in all age groups with the level of significance of (P = 0.013). No significant relation was found between age and MMO with a P of (>0.05), but a significant correlation was found between MMO and body weight and height with a P of (<0.01).